Association between infection prevention and control safety culture and healthcare workers’ compliance with infection control measures: a cross-sectional study - Cen, Yisui; Lao, Chuyu; Li, Zihuan; Zhao, Huiwen; Wang, Tian; Fan, Cuiqiong; Liu, Baohong; Zhao, Zhenyao; Zou, Ya; Lin, Guanwen (Frontiers in Public Health, 2025)
BackgroundInfection prevention and control (IPC) safety culture is recognized as a crucial factor in improving healthcare workers’ (HCWs) compliance with IPC measures. Despite its importance, evidence regarding the influence of IPC safety culture on compliance remains limited and warrants further investigation.MethodsA cross-sectional study was conducted from March 27 to April 3, 2025, using an online questionnaire to examine the association between IPC safety culture and HCWs’ compliance with IPC measures across more than 200 healthcare institutions, including 12 tertiary hospitals, in Haizhu District, Guangzhou, Guangdong Province, China. IPC safety culture was assessed using the Infection Control Culture Scale, while compliance with IPC measures was measured with the Compliance with Standard Precautions Scale, both utilizing five-point Likert scales. Student’s t test assessed differences between groups, and linear correlation analyses examined relationships between IPC safety culture dimensions and compliance scores. Multivariate logistic regression was used to identify factors associated with HCWs’ compliance to IP measures.ResultsA total of 1,600 questionnaires were distributed, of which 1,471 were valid (91.94%). HCWs aged over 30 years, with more than 5 years of work experience, and holding a Master’s degree or higher had higher IPC safety culture scores compared with their counterparts (p < 0.05). Similarly, HCWs aged over 30 years, with more than 5 years of experience, a Master’s degree or higher, and possessing clinical teaching qualifications demonstrated higher compliance with IPC measures compared with their counterparts (p < 0.05). Linear correlation analysis showed that basic IPC competence was strongly correlated with all dimensions of IPC compliance (r = 0.70, 0.63, 0.62, 0.63, 0.64, and 0.58, p < 0.001). Hospital management climate, departmental team cooperation, organizational learning and continuous improvement, and reporting frequency of hospital-acquired infections (HAIs) adverse events were weakly to moderately correlated with IPC compliance (p < 0.001). Based on a median score of 4.95 (IQR 4.77–5.00), 840 participants (57.10%) were classified as having good compliance, and 631 (42.90%) as poor compliance. Multivariate logistic regression indicated that clinical instructor status (OR = 1.60, 95% CI: 1.46–1.79), basic IPC competence (OR = 1.87, 95% CI: 1.73–1.99), hospital management climate (OR = 1.50, 95% CI: 1.08–2.10), reporting frequency of HAIs adverse events (OR = 1.36, 95% CI: 1.19–1.54), and organizational learning and continuous improvement (OR = 3.59, 95% CI: 2.68–4.80) as independent predictors of IPC compliance.ConclusionIPC safety culture significantly affects HCWs’ adherence to IPC measures. Enhancing basic IPC competence, hospital management support, organizational learning, reporting practices, and targeted interventions for clinical instructors can improve compliance and help prevent HAIs.